Estimasi Nilai Faktor Intensitas Tegangan (KI) Tipe Center Crack Dengan Metode Numerik - Firmansyah, Hendrix Noviyanto (SENATIK STT Adisutjipto, 2016)
Crack on a structure will lead to hazard if it’s ignored, because It’s causing singularity to the tip of the cracked structure where the stress tend to infinity. Stress Intensity Factors(SIF) will determine the behaviour of the cracked structure, and it have have to figure it out. Many methods can estimate or predict the values of the SIF according to the crack mode and the crack types. Numerical mothod such as displacement extrapolation and Virtual crack closure technique is one of those method. Method of displacement extrapolation and VCCT in this research will estimate the value of the KI (SIF)of the mode I (opening mode) center type crack. Modelling and analyzing in a FEM based software is needed to accuire datas to calculate the KI. Nodal displacement and nodal force are those datas. Result shows that the displacement extrapolation method have small eror to the value of KI than the VCCT. Displacement extrapolation method also give simple calculaton than the VCCT. In order for VCCT method to be acurate, remeshing model is needed.